Impact of Antimicrobial Stewardship and Infection Prevention and Control Programmes on Antibiotic Usage and A. baumannii resistance: A 2016–2023 Multicentre Prospective Study - Liu L; Liu B; Li L; Li Y; Zhou X; Li Q (Infection and Drug Resistance)
Lei Liu,1,2,* Bin Liu,1,2,* Liang Li,1,2 Yu Li,3 Xiangdong Zhou,1,2 Qi Li1,2 1Department of Respiratory Medicine, The First Affiliated Hospital, Hainan Medical University, Haikou, Hainan, People’s Republic of China; 2Hainan Province Clinical Medical Center of Respiratory Disease, Haikou, Hainan, People’s Republic of China; 3Department of Respiratory Medicine, The Fourth Affiliated Hospital, Harbin Medical University, Harbin, Heilongjiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qi Li, Email lqlq198210@sina.comObjective: This study assesses the efficacy of antimicrobial stewardship (AMS) and infection prevention and control programmes (IPCP) in guiding the use of antibiotics and the control of A. baumannii (AB) resistance at multiple medical centres.Methods: We evaluated the effectiveness of the policy on antibiotic consumption and AB resistance by determining the relationship between the defined daily doses (DDD) for antibiotics – or alcohol-based hand gel (ABHG) consumption – and the incidence of carbapenem-resistant AB (CR-AB), multidrug-resistant AB (MDR-AB) and extensively drug-resistant AB (XDR-AB) at two medical centers from 2016– 2023.Results: In total, 4057 AB isolates were collected; 64.95% of the AB isolates were CR, 59.48% were MDR and 1.41% were XDR. The major categories of the AB clinical strains collected were extracted primarily from patients’ respiratory tract specimens, the ICU wards and patients over 65 years old, accounting for 76.98%, 67.98% and 63.72%, respectively. The incidence of CR-AB, MDR-AB and XDR-AB based on AMS and IPCP measures ranged from 70.04% to 58.42% (P< 0.0001), 64.26% to 52.16% (P< 0.0001) and 2.27% to 0.60% (P=0.0167), respectively. The DDD of total antibiotics administered per 1000 patient days (PD) decreased significantly from 51.25± 4.22 to 40.92± 2.48 (P< 0.0001), and ABHG consumption per 1000 PD increased significantly from 5.25± 0.98 to 13.51± 5.12 (P< 0.0001). We found a statistically significant positive correlation between the DDD of antibiotic consumption and the incidence of CR-AB, MDR-AB and XDR-AB (r=0.9755 and P< 0.0001, r=0.9571 and P=0.0002, r=0.9230 and p=0.0011, respectively). In addition, a statistically negative correlation was found between ABHG consumption and the incidence of CR-AB, MDR-AB, and XDR-AB (r=− 0.9473 and P=0.0004, r=− 0.9123 and P=0.0016, r=− 0.9138 and P=0.0015, respectively).Conclusion: Comprehensive AMS and IPCP intervention measures can successfully achieve a sustained amelioration in the resistance and transmission of CR-AB, MDR-AB and XDR-AB, which are regarding potential applicability to other hospitals.Keywords: Acinetobacter baumannii, antibiotic resistance, antimicrobial stewardship, infection prevention and control programmes